76.3k views
10 votes
Find the remainder when the function


x^(3) + 2 {x}^(2) - 3x + 4


1 Answer

11 votes

Answer:

The correct answer is = 10

Step-by-step explanation:

Given:
x^(3) + 2 {x}^(2) - 3x + 4

Formula/Theorem using:

Remainder theorem = if the polynomial p(x) is divided by the binomial x-a then p(a) will be the remainder.

Solution:

using remainder theorem;

p(x) =
x^(3) + 2 {x}^(2) - 3x + 4

divided by binomial x+2, then

p(-2) =
(-2)^(3) + 2 (-2)^(2) - 3(-2) + 4

= -8 + 8 + 6 + 4

= 10

User Agrajag
by
5.5k points